Ubiquitin Associates with the N‐Terminal Domain of Nerve Growth Factor: The Role of Copper(II) Ions. Issue 49 (19th October 2016) - Lanza, Valeria; Travaglia, Alessio; Malgieri, Gaetano; Fattorusso, Roberto; Grasso, Giuseppe; Di Natale, Giuseppe; Zito, Valeria; Arena, Giuseppe; Milardi, Danilo; Rizzarelli, Enrico
Abstract: Many biochemical pathways involving nerve growth factor (NGF), a neurotrophin with copper(II) binding abilities, are regulated by the ubiquitin (Ub) proteasome system. However, whether NGF binds Ub and the role played by copper(II) ions in modulating their interactions have not yet been investigated. Herein NMR spectroscopy, circular dichroism, ESI‐MS, and titration calorimetry are employed to characterize the interactions of NGF with Ub. NGF1–14, which is a short model peptide encompassing the first 14 N‐terminal residues of NGF, binds the copper‐binding regions of Ub ( K D =8.6 10 −5  m ). Moreover, the peptide undergoes a random coil–polyproline type II helix structural conversion upon binding to Ub. Notably, copper(II) ions inhibit NGF1–14 /Ub interactions. Further experiments performed with the full‐length NGF confirmed the existence of a copper(II)‐dependent association between Ub and NGF and indicated that the N‐terminal domain of NGF was a valuable paradigm that recapitulated many traits of the full‐length protein. Abstract : A copper‐dependent partnership : The existence of a copper(II)‐dependent physical association between ubiquitin and nerve growth factor (NGF) is reported (see figure). These results provide clues for a deeper understanding of the network of intertwined pathways that regulate metal homeostasis and neuronal development.